THE PLACE OF SACRAMENTAL ART IN ALISHER NAVOI’S “PANDNOMA” - Bafoeva Maftuna Botir kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article analyses one of the best masterpieces of Alisher Navoi’s “PANDNOMA” and the place of sacramental art in it.